Fenretinide Improves Intestinal Barrier Function and Mitigates Alcohol Liver Disease - Tang, Xiao-Han; Melis, Marta; Mai, Karen; Gudas, Lorraine J.; Trasino, Steven E. (Frontiers in Pharmacology, 2021)
Alcohol liver disease (ALD) is a major cause of liver‐related diseases, yet there remains an unmet demand for ALD drugs. The pathogenesis of ALD involves perturbations to the intestinal barrier and translocation of bacterial endotoxin, which promotes hepatic inflammation and progression of ALD through toll-like receptor 4 (TLR4). Here we investigated the ability of fenretinide (Fen) [N-(4-hydroxyphenyl) retinamide], a retinoid with known anti-cancer and anti-inflammatory properties, to modulate intestinal permeability and clinical hallmarks of ALD in a mouse model of ethanol (EtOH) exposure. Our results show that EtOH-treated mice had reductions in mRNA and protein expression of intestinal tight junction proteins, including claudin 1 and occludin, and increases in intestinal permeability and endotoxemia compared to pair-fed mice. Also, EtOH-treated mice had marked increases in hepatic steatosis, liver injury, and expression of pro-inflammatory mediators, including TNF-α, and TLR4-positive macrophages in the intestines and liver, respectively. In contrast, EtOH+Fen-treated mice were resistant to the effects of EtOH on promoting intestinal permeability and had higher intestinal protein levels of claudin 1 and occludin. Also, EtOH+Fen-treated mice had lower plasma levels of endotoxin, and reductions in both intestinal and hepatic expression of TNF-α and TLR4 positive macrophages in the intestine and liver. Lastly, we found that EtOH+Fen-treated mice exhibited major reductions in hepatic triglycerides and liver injury. Our findings are the first to demonstrate that fenretinide possesses anti-ALD properties, potentially through modulation of the intestinal barrier function, endotoxemia, and TLR4-mediated inflammation. These data warrant further pre-clinical investigations of fenretinide as a potential anti-ALD drug.